Comparison of two mouse ameloblast-like cell lines for enamel-specific gene expression - Sarkar, Juni; Simanian, Emil J.; Tuggy, Sarah Y.; Bartlett, John D.; Snead, Malcolm L.; Sugiyama, Toshihiro; Paine, Michael L. (Frontiers in Physiology, 2014)
Ameloblasts are ectoderm-derived cells that produce an extracellular enamel matrix that mineralizes to form enamel. The development and use of immortalized cell lines, with a stable phenotype, is an important contribution to biological studies as it allows for the investigation of molecular activities without the continuous need for animals. In this study we compare the expression profiles of enamel-specific genes in two mouse derived ameloblast-like cell lines: LS8 and ALC cells. Quantitative PCR analysis indicates that, relative to each other, LS8 cells express greater mRNA levels for genes that define secretory-stage activities (Amelx, Ambn, Enam and Mmp20), while ALC express greater mRNA levels for genes that define maturation-stage activities (Odam and Klk4). Western blot analyses show that Amelx, Ambn and Odam proteins are detectable in ALC, but not LS8 cells. Unstimulated ALC cells form calcified nodules, while LS8 cells do not. These data provide greater insight as to the suitability of both cell lines to contribute to biological studies on enamel formation and biomineralization, and highlight some of the strengths and weaknesses when relying on enamel epithelial organ-derived cell lines to study molecular activities of amelogenesis.